2022
DOI: 10.1155/2022/2468114
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of Risk Factors for Intraoperative Hypotension in Cesarean Section and Poor Prognosis of Neonates

Abstract: Objective. To analyze the risk factors of intraoperative hypotension in cesarean section women and poor prognosis of neonates. Methods. The clinical data of 1071 cesarean section women admitted to The Affiliated Jiangning Hospital of Nanjing Medical University from January 2021 to December 2021 were retrospectively analyzed. They were divided into hypotension group ( n = 472 ) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…This finding is consistent with a study at Sriraj Hospital stating that a high dose of bupivacaine is a modifiable risk factor for SAIH [14]. Although our study showed no association between the SA puncture and hypotension level, another study indicated that the SA puncture level at L2-L3 is associated with hypotension [18].…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with a study at Sriraj Hospital stating that a high dose of bupivacaine is a modifiable risk factor for SAIH [14]. Although our study showed no association between the SA puncture and hypotension level, another study indicated that the SA puncture level at L2-L3 is associated with hypotension [18].…”
Section: Discussionsupporting
confidence: 92%
“…Subsequently, a detailed examination of full-text articles resulted in the exclusion of 14 studies. Ultimately, 12 studies successfully satisfied the established criteria and were included in the review [15,17,18,[22][23][24][25][26][27][28][29][30]. The characteristics of the 11 studies involving 2009 patients are summarized in Table 1.…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 99%
“…Patient-related factors include advanced age, pregnancy, obesity, diabetes mellitus (DM), anemia, and hypertension. On the other hand, technical considerations include the presence of a block level at or above T5, administration of large doses of local anesthetics, and use of opioids during premedication ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%